Lean Management as an Innovation to Reduce Complaint Handling Time in Hospital X - Munaa, Nihayatul; Faiz, Faizatul Ummah; Rahmawati, Nahardian Vica; Rateh, Nali (Inovasi Lokal, 2023)
Customer service is a service product from Hospital X. The better the service at a hospital, the number of complaints will decrease. In the customer service flow for Hospital X there is Complaint Handling and monitoring and evaluation. The purpose of this research is to provide lean management innovation as an effort to reduce the waiting time for complaint handling. In this study the method used was community service with the time period April-July 2023 at Hospital X. The column for patient complaints at the hospital was not clear and detailed. So the added innovation is to cut steps or steps that lack value by creating or adding a complaint menu on the Hospital website. The complaints menu contains information and complaints services